2022
DOI: 10.1021/acs.jmedchem.2c01195
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Highly Potent Transthyretin Amyloidogenesis Inhibitor: Design, Synthesis, and Evaluation

Abstract: Transthyretin amyloidosis (ATTR) is a group of fatal diseases described by the misfolding and amyloid deposition of transthyretin (TTR). Discovering small molecules that bind and stabilize the TTR tetramer, preventing its dissociation and subsequent aggregation, is a therapeutic strategy for these pathologies. Departing from the crystal structure of TTR in complex with tolcapone, a potent binder in clinical trials for ATTR, we combined rational design and molecular dynamics (MD) simulations to generate a serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 100 publications
1
15
0
Order By: Relevance
“…As expected for specific binding, integration of the titration peaks produced a sigmoidal enthalpy curve for each interaction (Figure 5 Previous ITC studies used different models for interpolating ITC data. The calorimetric data of the binary complexes of tafamidis with TTR were interpolated using a sequential model [12,18], revealing a strong negative cooperativity between the two binding sites. The result showed that the first binding site had an extremely low K d ' of 9.9 nM and a ΔH = -6.0 kcal mol -1 , while the second binding site resulted in a loss of affinity with a very high K d " of 260 nM and a ΔH = -6.5 kcal mol -1 .…”
Section: -Omt and Its Lipophilic Analogues Stabilise Ttr In Humanmentioning
confidence: 99%
See 3 more Smart Citations
“…As expected for specific binding, integration of the titration peaks produced a sigmoidal enthalpy curve for each interaction (Figure 5 Previous ITC studies used different models for interpolating ITC data. The calorimetric data of the binary complexes of tafamidis with TTR were interpolated using a sequential model [12,18], revealing a strong negative cooperativity between the two binding sites. The result showed that the first binding site had an extremely low K d ' of 9.9 nM and a ΔH = -6.0 kcal mol -1 , while the second binding site resulted in a loss of affinity with a very high K d " of 260 nM and a ΔH = -6.5 kcal mol -1 .…”
Section: -Omt and Its Lipophilic Analogues Stabilise Ttr In Humanmentioning
confidence: 99%
“…The effect of adding an extra methyl to 3-OMT in the non-phenolic ring worsen the affinity in derivative 1 even further and restores in derivative 2 the high affinity observed for tolcapone, accompanied by higher permeability and selectivity than 3-OMT, hence of tolcapone (Table 4). The enhanced ability to penetrate the blood-brain barrier represents a major key point in developing a treatment for CNS TTR amyloidosis, such as familial leptomeningeal amyloidosis [59,60], as demonstrated by the studies attempting to increase the penetration both in the brain and in the periphery of tafamidis [61] and tolcapone itself [18].…”
Section: Overall Performance Of 3-omt and Its Lipophilic Analogues In...mentioning
confidence: 99%
See 2 more Smart Citations
“…A first clinical trial of CRISPR/Cas9 has recently been performed with successful results in the reduction of TTR production in humans . Currently, work is ongoing to better diagnose patients early, to follow up and monitor the various available treatments, and to find improved small-molecule ligands as kinetic stabilizers. …”
Section: Introductionmentioning
confidence: 99%